Immune inhibitory proteins and their pathogenic and therapeutic implications in autoimmunity and autoimmune hepatitis - Albert J. Czaja (Taylor & Francis Group, 2019)
Key inhibitory proteins can blunt immune responses to self-antigens, and deficiencies in this repertoire may promote autoimmunity. The goals of this review are to describe the key immune inhibitory proteins, indicate their possible impact on the development of autoimmune disease, especially autoimmune hepatitis, and encourage studies to clarify their pathogenic role and candidacy as therapeutic targets. English abstracts were identified in PubMed by multiple search terms. Full length articles were selected for review, and secondary and tertiary bibliographies were developed. Cytotoxic T lymphocyte antigen-4 impairs ligation of CD28 to B7 ligands on antigen presenting cells and inhibits the adaptive immune response by increasing anti-inflammatory cytokines, generating regulatory T cells, and reducing T cell activation and proliferation. Programed cell death antigen-1 inhibits T cell selection, activation, and proliferation by binding with two ligands at different phases and locations of the immune response. A soluble alternatively spliced variant of this protein can dampen the inhibitory signal. Autoimmune hepatitis has been associated with polymorphisms of the cytotoxic T lymphocyte antigen-4 gene, reduced hepatic expression of a ligand of programed cell death antigen-1, an interfering soluble variant of this key inhibitory protein, and antibodies against it. Findings have been associated with laboratory indices of liver injury and suboptimal treatment response. Abatacept, belatacept, CD28 blockade, and induction of T cell exhaustion are management considerations that require scrutiny. In conclusion, deficiencies in key immune inhibitory proteins may promote the occurrence of autoimmune diseases, such as autoimmune hepatitis, and emerging interventions may overcome these deficiencies. Investigations should define the nature, impact and management of these inhibitory disturbances in autoimmune hepatitis.